2020
DOI: 10.26508/lsa.202000683
|View full text |Cite
|
Sign up to set email alerts
|

Snail augments fatty acid oxidation by suppression of mitochondrial ACC2 during cancer progression

Abstract: Despite the importance of mitochondrial fatty acid oxidation (FAO) in cancer metabolism, the biological mechanisms responsible for the FAO in cancer and therapeutic intervention based on catabolic metabolism are not well defined. In this study, we observe that Snail (SNAI1), a key transcriptional repressor of epithelial–mesenchymal transition, enhances catabolic FAO, allowing pro-survival of breast cancer cells in a starved environment. Mechanistically, Snail suppresses mitochondrial ACC2 (ACACB) by binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Given that TGFβ1-induced activation of Smad3 is also a key signaling event leading to EMT, this study also suggests that FAO depression may occur secondary or in parallel to EMT. Supporting this, it has been reported that upregulation of Snail, a major regulator of EMT, correlated with the downregulation of critical genes involved in FAO expression in hepatocellular carcinomas (Tanaka et al, 2013); pharmacological inhibition of FAO reverses Snail-mediated metabolic reprogramming in vivo and progression of breast cancer (Yang et al, 2020). Future studies are needed to elucidate the role of EMT in the regulation of FAO or other metabolic alteration in the kidney after fibrotic injuries.…”
Section: Metabolic Alternationmentioning
confidence: 79%
“…Given that TGFβ1-induced activation of Smad3 is also a key signaling event leading to EMT, this study also suggests that FAO depression may occur secondary or in parallel to EMT. Supporting this, it has been reported that upregulation of Snail, a major regulator of EMT, correlated with the downregulation of critical genes involved in FAO expression in hepatocellular carcinomas (Tanaka et al, 2013); pharmacological inhibition of FAO reverses Snail-mediated metabolic reprogramming in vivo and progression of breast cancer (Yang et al, 2020). Future studies are needed to elucidate the role of EMT in the regulation of FAO or other metabolic alteration in the kidney after fibrotic injuries.…”
Section: Metabolic Alternationmentioning
confidence: 79%
“…In glucose-deficient conditions, which represent the metabolic status of the metastatic procedure, Snail specifically activates catabolic reprogramming. We have reported that Snail directly suppresses PFKP and ACC2 transcription, thereby switching the glycolytic flux into the PPP to enhance NADPH generation and stimulate oxidative phosphorylation via FAO, respectively [16,18]. ACC2 levels varied among breast cancer molecular subtypes in clinical samples, in an inverse relation to Snail with a reliance on p53 status.…”
Section: Paradox Of Snail-mediated Catabolic Metabolismmentioning
confidence: 97%
“…The basal-like subtype shows a higher p53-loss rate along with increased Snail abundance than do the luminal subtypes (mainly p53 wild type) [18,61,66]. As the triple negative breast cancers (TNBC) have an aggressive clinical course and lack treatment options, there have been various attempts to unravel their pathogenesis.…”
Section: Breast Cancer Subtypes Use Different Metabolic Circuit To Gamentioning
confidence: 99%
See 2 more Smart Citations